Identification of Electrode Respiring, Hydrocarbonoclastic Bacterial Strain Stenotrophomonas maltophilia MK2 Highlights the Untapped Potential for Environmental Bioremediation - Venkidusamy, Krishnaveni; Megharaj, Mallavarapu (Frontiers in Microbiology, 2016)
Electrode respiring bacteria (ERB) possess a great potential for many biotechnological applications such as microbial electrochemical remediation systems (MERS) because of their exoelectrogenic capabilities to degrade xenobiotic pollutants. Very few ERB have been isolated from MERS, those exhibited a bioremediation potential towards organic contaminants. Here we report once such bacterial strain, Stenotrophomonas maltophilia MK2, a facultative anaerobic bacterium isolated from a hydrocarbon fed MERS, showed a potent hydrocarbonoclastic behavior under aerobic and anaerobic environments. Distinct properties of the strain MK2 were anaerobic fermentation of the amino acids, electrode respiration, anaerobic nitrate reduction and the ability to metabolize n-alkane components (C8-C36) of petroleum hydrocarbons including the biomarkers, pristine and phytane. The characteristic of diazoic dye decolorization was used as a criterion for pre-screening the possible electrochemically active microbial candidates. Bioelectricity generation with concomitant dye decolorization in MERS showed that the strain is electrochemically active. In acetate fed microbial fuel cells, maximum current density of 273±8 mA/m2 (1000Ω) was produced (power density 113±7 mW/m2) by strain MK2 with a coulombic efficiency of 34.8 %. Further, the presence of possible alkane hydroxylase genes (alkB and rubA) in the strain MK2 indicated that the genes involved in hydrocarbon degradation are of diverse origin. Such observations demonstrated the potential of facultative hydrocarbon degradation in contaminated environments. Identification of such a novel petrochemical hydrocarbon degrading ERB is likely to offer a new route to the sustainable bioremedial process of source zone contamination with simultaneous energy generation through MERS.